Corrosion resistance of pack chromized Fe-Mn-Al-Si-C steel - Casteletti, Luiz Carlos; Takeya, Gustavo Satoru; Neto, Amadeu Lombardi; Picon, Carlos Alberto [UNESP]; Totten, George Edward (My University, 2015)
Austenitic Fe-Mn-Al-Si-C stainless steel alloys provide excellent cold formability and lower density compared to conventional stainless steels. These steels owe their corrosion and oxidation resistance to their aluminum and silicon contents and the stability of their gamma-phase due to the manganese and carbon alloying elements. The coating of this steel with chromium can increase its corrosion resistance further and a pack chromising treatment offers an environmentally friendly alternative to hard chromium when additional wear and corrosion resistance is needed. In this work, steel samples with a composition of Fe-31Mn-7.5Al-1.3Si-0.9C were subjected to pack cromising treatment for 2 and 3 hours at 950°C. The composition of the powder was 25% of metallic Cr (>150 mesh), 69%Al2O3 and 6% NH4Cl. The treated samples were analyzed by optical and electron microscopy, microhardness measurements, wear and corrosion tests.
Keywords: Chromizing; Corrosion; Fe-Mn-Al-Si-C steel; Wear